3D shape and size analysis of the humerus in four rat strains: A comparative study with humans - Yasemin Üstündağ; Yasin Demiraslan; Osman Yılmaz (Jurnal Medik Veteriner, 2026)
Translational anatomy is a field dedicated to converting fundamental scientific research into clinical applications. The rat humerus is one of the important bones used in the development of new techniques, the evaluation of pathophysiology, and the design of treatment interventions. This study aimed to provide accurate reference data on humeral morphology and to identify differences in humeral morphology among various rat strains. Morphologic, morphometric, and geometric morphometric methods were employed. For this purpose, a total of forty-eight humeri from the most commonly used laboratory rat strains were compared across strains and with humans. According to the statistical results, significant differences were observed between the groups in terms of greatest length, greatest length of the lateral part, greatest length of the medial part, width of the diaphysis, and length of the trochlea (p < 0.05). The breadth of the proximal end was greatest in the Wistar Albino strain, whereas the other strains exhibited smaller values. However, based on the principal component 1 results, the highest variation was observed in the Lewis strain, while the lowest variation was found in the Wistar Albino strain. In the overall shape analysis, Brown Norway was similar to Wistar Albino, whereas Sprague Dawley was similar to Lewis. The Wistar Albino strain appears suitable for proximal humeral studies, the Brown Norway strain for investigations focusing on shaft circumference, and the Sprague Dawley and Lewis strains for distal humeral studies. These findings are expected to contribute to the development of new shoulder prostheses, pins, external fixator materials, and innovative surgical techniques.